On and off-the-record correction practices: A survey-based study of how chemistry researchers react to errors - Bordignon, Frédérique (Accountability in Research, 2025)
AIM: This survey-based study (982 participants) explores chemistry researchers' practices and motivations in correcting errors in scientific publications. RESULTS: While respondents believe errors should be corrected in principle, practical challenges arise due to scientific, social, and pragmatic factors. These include the perceived seriousness of the error, its scientific impact, the age of the publication, and the time required. Difficulties also stem from criticizing others, especially senior colleagues. Despite these challenges, researchers are motivated to correct errors to limit their spread, contribute to the common good, and advance their own work. Researchers prefer informal error correction through private correspondence, discussions with colleagues, or teaching situations, over formal corrections to the scholarly record. The peer-review stage is crucial for detecting and correcting errors, but it is criticized for its deficiencies, including lack of professionalism among reviewers and editors. Some authors yield to reviewer pressure knowingly introducing changes that are clearly wrong. While the low participation rate (2%) does not allow generalization, the study shows that science correction is complex, involving a continuum of practices. CONCLUSION: To improve science correction, the study suggests that online platforms and repositories can facilitate the transition from off-the-record discussions to on-the-record initiatives, ultimately feeding into the public record.